Multinational Firms in the World Economy - Navaretti, Giorgio Barba (Princeton University Press, 2020)
Depending on one's point of view, multinational enterprises are either the heroes or the villains of the globalized economy. Governments compete fiercely for foreign direct investment by such companies, but complain when firms go global and move their activities elsewhere. Multinationals are seen by some as threats to national identities and wealth and are accused of riding roughshod over national laws and of exploiting cheap labor. However, the debate on these companies and foreign direct investment is rarely grounded on sound economic arguments. This book brings clarity to the debate. With the contribution of other leading experts, Giorgio Barba Navaretti and Anthony Venables assess the determinants of multinationals' actions, investigating why their activity has expanded so rapidly, and why some countries have seen more such activity than others. They analyze their effects on countries that are recipients of inward investments, and on those countries that see multinational firms moving jobs abroad. The arguments are made using modern advances in economic analysis, a case study, and by drawing on the extensive empirical literature that assesses the determinants and consequences of activity by multinationals. The treatment is rigorous, yet accessible to all readers with a background in economics, whether students or professionals. Drawing out policy implications, the authors conclude that multinational enterprises are generally a force for the promotion of prosperity in the world economy.